SISTEM PENDUKUNG KEPUTUSAN KLINIS MANAJEMEN NEONATAL BERBASIS ALGORITMA MTBS - R. N. Karimah; R.r. Lia Chairina; A.P. Wicaksono (Jurusan Teknologi Informasi Politeknik Negeri Jember, 2019)
The neonatal period is an important period in life. Infant Mortality Rate (IMR) is the number of infant deaths in the first 28 days of life (neonatal) per 1000 live births (PERMENKES No 53, 2014). IMR in Indonesia is still high compared to other ASEAN countries, data in 2016 shows that IMR reaches 25.5, it’s meaning that there are around 25.5 deaths per 1,000 babies born (BPS, 2016). Poor neonatal management clinically will cause abnormalities, and can even lead to lifelong disability, and death, while administratively can cause legal problems. Neonatal management requires complete clinical data support, relevance, accurate and timeliness aspects. This research is a mixed method research with action research approach and prototype method in the development of Clinical Decision Support System (CDSS). This study produced CDSS based on Integrated Childhood Illness Management (IMCI) algorithm for neonatal service management in primary health care center. The results of testing system using black-box technique is accordance with the requirements and obtained a valid overall result. DSS IMCI can be integrated with Electronic Health Record (EHR) so can occur for appropriate clinical decision making.